Design, Static Analysis and Fabrication of Composite Joints - Manikandan, J.; Yusuf Mubin, A. (International Journal of Psychosocial Rehabilitation, 2019)
The bonded joints will have one of the important issues in the composite technology: the repair of aging in aircraft applications. In these applications and also for joining various composite material parts together, the composite materials are fastened together either using adhesives or mechanical fasteners. In this paper, we have carried out design, static analysis of 3-D models, and fabrication of the composite joints (bonded, riveted, and hybrid). The 3-D model of the composite structure will be fabricated by using materials such as epoxy resin, glass fibre material, and aluminium rivet for preparing the joints. The static analysis was carried out with different joints by using ANSYS software. After fabrication, a parametric study was also conducted to compare the performance of the hybrid joint with varying adherent width, adhesive thickness, and overlap length. Different joints and their materials tensile test results have been compared.